2013
DOI: 10.4238/2013.march.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation negatively correlated with mRNA expression but not tissue differential expression after heat stress

Abstract: ABSTRACT. DNA methylation plays a central role in gene expression. In this study, we detected the promoter methylation pattern of the chicken heat shock protein 70 (HSP70) gene and its association with messenger RNA (mRNA) expression before and after heat shock. The results showed that mRNA expression increased in response to heat stress and peaked at 3 h before dropping. Hypomethylation of the HSP70 promoter occurred in all of the groups studied, but the difference between groups within tissue type was not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
6
14
0
Order By: Relevance
“…This finding suggests that hypomethylation is needed for up‐regulation/production of Hsps as observed by a marked increase in the Hsp70 level in this T‐F0 group. This is in accordance with the results of Gan et al (67), who demonstrated that DNA methylation of the Hsp70 promoter was negatively associated with the mRNA expression level of hsp70 in the muscle tissue of chicken. However, the reduced DNA methylation might be a prerequisite for the observed increase histone acetylation (68, 69).…”
Section: Discussionsupporting
confidence: 93%
“…This finding suggests that hypomethylation is needed for up‐regulation/production of Hsps as observed by a marked increase in the Hsp70 level in this T‐F0 group. This is in accordance with the results of Gan et al (67), who demonstrated that DNA methylation of the Hsp70 promoter was negatively associated with the mRNA expression level of hsp70 in the muscle tissue of chicken. However, the reduced DNA methylation might be a prerequisite for the observed increase histone acetylation (68, 69).…”
Section: Discussionsupporting
confidence: 93%
“…The results of level of Hsp-70 mRNA in various tissues, viz., heart, liver, bursa, spleen, and muscle revealed higher expression in the spleen. The expression of Hsp-70 is tissue-dependant in chickens subjected to heat treatment (26)(27)(28)20) which was true in the present study also. Blake et al (29) reported that different tissues responded differently to heat and=or cold stress and with age, which substantiates the present findings.…”
Section: ãããsupporting
confidence: 67%
“…Hyperthermia induced by exposure to heat appears to increase the activity and amount of heat shock transcription factor, enhancing the Hsp-70 mRNA synthesis leading to high concentrations in N birds; whereas, the birds already exposed could tolerate the hyperthermia and effectively reduce the heat shock transcription factor resulting in low levels of Hsp gene expression and better tolerance to heat stress. The possible reason for higher gene expression in normal birds might be that the Hsp-70 gene has no intron (20), which hastens the transcription process after heat shock, and it increases further with gradual heat stress, resulting in higher expression of Hsp-70 in N birds. The present findings were in accordance with the reduced expression of Hsp-70 observed in chick embryos exposed to increased temperature from day 4 to 12 (21).…”
Section: ãããmentioning
confidence: 97%
“…These results are in accordance with those of Gan et al . () who demonstrated hypomethylation of CpG islands present in a proximal promoter part of the chick HSP70 gene (Gan et al . ).…”
Section: Discussionmentioning
confidence: 99%